Transformational leadership and job satisfaction: The mediating effects of perceptions of politics and market orientation in the Japanese context - Takuma Kimura (International Journal of Business Science & Applied Management (IJBSAM), 2012)
This paper investigates the causal relationship among transformational leadership, perceptions of organizational politics, market orientation, and work-related outcome. In this study, we assumed that organization-level perceptions of organizational politics and market orientation mediate the relationship between top management's transformational leadership and employees' work-related outcomes and that perceptions of organizational politics diminish market orientation. Data were collected from a sample of 200 employees working in Japanese companies. To test the hypothesized correlations, we used structural equation modelling using AMOS 16.0. As we hypothesized, both perceptions of politics and market orientation mediated the relationship between transformational leadership and employees' job satisfaction. However, contrary to our expectation, perceptions of organizational politics were not significantly correlated with market orientation. This study is the first empirical research of organizational politics using a Japanese sample. In future studies, we should resolve methodological limitations of this study and develop theoretical frameworks that reflect cultural difference among countries.
Keywords: 650; transformational leadership; organizational politics; market orientation; job satisfaction